Pola Hidup Nelayan Migran di Pelabuhan Pantai Sadeng Kecamatan Girisubo Kabupaten Gunung Kidul DIY - Lathifah, Af’idatul; Christianti, Lydia (Studi Budaya Nusantara, 2018)
Abstract The fishery sector is one of the economic sectors that is currently being intensively perceived by the government of Indonesia. One of the existing fish port is the Port of Sadeng Beach in Girisubo District Gunung Kidul Regency. As an artificial harbor, Sadeng Beach does not have human resources as a fisherman, so emerging migrant fishermen are imported from other provinces in Indonesia. The life of migrant fishermen who are migrants in Gunung Kidul have different patterns with local fishermen. Fisherman profession is the main profession, so the migrant fishermen prefer to use large boats and sail for days. The agenda for returning home is done on average twice a year when the seasons are not good. Migrant fishermen settlements are also non-permanent settlements, they only rent from local government. In addition, there is also a culture of sea alms that previously did not have cultural roots from local residents, so that the implementation of sea alms also varied from time to time.